Ali Pasha Tepelena in the Turkish Historiography of Republican Era and Morean Uprising of 1821 - (:unkn) unknown (My University, 2012)
0

Ali Pasha Tepelena, who is known for his role in 1821 Morean uprising in addition to his identity as Pasha of Iannina in the Turkish Historiography of Republican era, has been mainly included in historical studies on the 19th century Greek nationalism. On the other hand political historiography of the 19th century Ottoman internal poitical developments includes limited amount of information about Ali Pasha under the topics relating to social order of the declining period as well as under those focusing on the era of Mahmud II, known for his efforts for strengthening central authority. These studies bring forward Ali Pasha both as a powerful noble of the period and as a rebellious character resisting to reforming efforts of Mahmud the Second. Role of such rebellious attitude of him in inciting the 1821 Morean uprising increases his importance in the Turkish historiograhpy. The fact that Ali Pasha Tepelena was dealt with predominantly in connection with the 1821 Morean uprising stirs up two problematic issues; one of them is that Ali Pasha gained increasing importance with his role in Morean uprising. This causes social, political and economic background of his power to be overlooked dramatically. Another issue is the praxis that 19th century separatist nationalist movements are read through a betrayal or loyalty perception. In many historical studies, this praxis confined Ali Pasha within a narrow point of view bordered by the questions asking if He was a betrayer or loyalist of the ottoman State due to his role in the 1821 Morean uprising. Our starting point taken to draw attention into these two issues is the fact that Ali Pasha is a prominent historical figure beyond his known role in the 1821 Morean uprising, showing political, economic and social conditions of the period he lived in.